PENDIDIKAN DAN PENILAIAN KARAKTER DI SEKOLAH MENENGAH KEJURUAN - Supriyadi, Edy (Jurnal Cakrawala Pendidikan, 2015)
Abstract: Character Education and its Assessment in Vocational High Schools. Character education is a process of helping people to develop good characters, such as honesty, responsibility, compassion, and self-respect. Character education at school aims to build the student and staff characters and to develop the school culture. The assessment of character education covers that of student and staff characters and the school culture. The assessment of student character can be conducted through classroom-based assessment by teachers. In addition, civic education and religion teachers are supposed to conduct the assessment of student character more thoroughly. The assessment of staff character should be conducted by a school internal team. The school culture may be assessed by a provincial external team. The results of assessment are used to make decisions of student grade promotion and graduation and to improve a character education program. Keywords: education, character education